36. INITIAL EVALUATION OF THE SCREENING PROCESS FOR INTESTINAL BACTERIA RESISTANT TO CARBAPENEM ANTIBIOTICS AT THE INFECTIOUS DISEASE DEPARTMENT OF VIET TIEP HOSPITAL, HAI PHONG (Vietnam Journal of Community Medicine, 2026)
Background: District hospitals are not equipped with microbiology laboratories and therefore cannot screen for Carbapenem - Resistant Enterobacteria (CRE).Objective: We initially evaluated a bedside CRE screening procedure that does not require a microbiology laboratoryMethod: 2 rectal swab specimens were collected for microbiological culture using bedside and microbiology laboratory procedures. For the clinical CRE screening procedure, we used a portable incubator made in Viet Nam to incubate agar at 37o C.Results: The positive rate of Carbapenem Resistant Enterobacteriacae was 17.4%, mainly Klebsiella spp in 90 cases. Notably, colonies grown in the homemade incubator showed larger size and density than those grown in the standard incubator, demonstrating affective thermos stability. Importantly, no contamination was observed on CRE-negative agar plates, confirming the reliability of the bedside sampling method.
Keywords: Bedside screening, Carbapenem Resistant Enterobactetiacae.